PENGARUH PEMBERIAN ISOLAT BAKTERI SELULOLITIK RUMEN KERBAU MELALUI AIR MINUM SEBAGAI SUMBER PROBIOTIK TERHADAP KARKAS ITIK BALI UMUR 8 MINGGU - D. W., Kurnia; Partama, I. B. G.; Bidura, I G. N. G. (Jurnal Peternakan Tropika, 2016)
The use of probiotics in the ration can increase the activity of enzymes and absorb of feed nutrient. Probiotics is a feed additive that can be given in ration or drinking water in the form of microorganisms that can live in the digestive tract, in symbiosis with the existing micro-organisms, is particularly useful and able to promote growth as well as the feed efficiency without undergoing the process of absorb. Based on the above, this study aimed to determine the effect of buffalo rumen cellulolytic bacteria in drinking water as a source of probiotics on the carcass weight of the 8-week aged Bali ducks. This research was conducted at Dajan Peken Village of Tabanan, Bali. The design used was completely randomized design (CRD) with three treatments and six replications . The variables measured were the slaughter weight, the carcass weight, the carcass percentage, consumption of rations and drinking water consumption. The three treatments namely: drinking water without cellulolytic bacteria as the control (A)  drinking water of 0.20% cellulolytic bacterial culture (B), and drinking water of 0.40% cellulolytic bacterial culture (C). The results showed that the administration of bacterial culture of cellulolytic of 0.20% and 0.40% through drinking water significantly (P <0.05) could increase the slaughter weight, the carcass weight, and the carcass percentage. Based on the research results, it can be concluded that the administration of probiotic bacteria isolates of cellulolytic buffalo rumen through drinking water at the level of 0.20% and 0.40% could increase the carcass of the 8 week aged Bali ducks.
Keywords: Bali ducks, cellulolytic bacteria, carcass weights, probiotics